Estimation of trophic niches in myrmecophagous spider predators - Dušátková, Lenka Petráková; Pekár, Stano; Michálek, Ondřej; Líznarová, Eva; Symondson, William O C (Scientific reports, 2020)
Among spiders, taxonomically the most diversified group of terrestrial predators, only a few species are stenophagous and feed on ants. The levels of stenophagy and ant-specialisation vary among such species. To investigate whether stenophagy is only a result of a local specialisation both fundamental and realised trophic niches need to be estimated. Here we investigated trophic niches in three closely-related spider species from the family Gnaphosidae (Callilepis nocturna, C. schuszteri, Nomisia exornata) with different levels of myrmecophagy. Acceptance experiments were used to estimate fundamental trophic niches and molecular methods to estimate realised trophic niches. For the latter two PCR primer sets were used as these can affect the niche breadth estimates. The general invertebrate ZBJ primers were not appropriate for detecting ant DNA as they revealed very few prey types, therefore ant-specific primers were used. The cut-off threshold for erroneous MOTUs was identified as 0.005% of the total number of valid sequences, at individual predator level it was 0.05%. The fundamental trophic niche of Callilepis species included mainly ants, while that of N. exornata included many different prey types. The realised trophic niche in Callilepis species was similar to its fundamental niche but in N. exornata the fundamental niche was wider than realised niche. The results show that Callilepis species are ant-eating (specialised) stenophagous predators, catching mainly Formicinae ants, while N. exornata is an ant-eating euryphagous predator catching mainly Myrmicinae ants.
Keywords: shluková analýza; predátorské chování; Polymerase Chain Reaction; polymerázová řetězová reakce; DNA; pavouci; Body Size; Predatory Behavior; Animals; Cluster Analysis; velikost těla; zvířata; Ants; Spiders; Formicidae